2020
DOI: 10.1016/j.renene.2019.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Used disposable nappies and expired food products valorisation through one- & two-stage anaerobic co-digestion

Abstract: Highlights  One-& two-stage anaerobic co-digestion of Disposable Nappies & EFP were compared  The highest H 2 production yield was observed in acidogenesis at HRT 2 d and pH 6.0  The highest CH 4 yield was observed in two-stage operation at HRT 25 d  Two-stage operation had 18.4% higher energy production than one-stage  COD removal reached 80% in the two-stage AD system *Highlights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 47 publications
2
15
0
1
Order By: Relevance
“…Sinbuathong et al (2012) reported that one of the advantages of phase separation is the ability to handle a higher organic loading rate than that in a single reactor. A similar study from Tsigkou et al (2020) found the same phenomenon, in that the application of a twostage digester treating co-digestion of used disposable nappies and expired food product at 60:40 (v/v) ratio, working at mesophilic condition (37±0.5°C) and 15 d HRT, the energy production was 18.5% higher than that in the single reactor.…”
Section: Methane Productionsupporting
confidence: 56%
See 1 more Smart Citation
“…Sinbuathong et al (2012) reported that one of the advantages of phase separation is the ability to handle a higher organic loading rate than that in a single reactor. A similar study from Tsigkou et al (2020) found the same phenomenon, in that the application of a twostage digester treating co-digestion of used disposable nappies and expired food product at 60:40 (v/v) ratio, working at mesophilic condition (37±0.5°C) and 15 d HRT, the energy production was 18.5% higher than that in the single reactor.…”
Section: Methane Productionsupporting
confidence: 56%
“…On the other hand, single-phase biodigester has also advantageous as it is a simple and straightforward operation and for an easier degradable substrate such as fruit and vegetable waste, single-phase process could be the preferred choice rather than two-phase reactor (Ganesh et al, 2014). Although previous studies have evaluated the AD process at ambient temperature (Minale & Worku, 2014;Wei et al, 2014;Murrugan & Appavu, 2018) and two-phase AD (Baldi et al, 2019;Tsigkou et al, 2020), to the best of our knowledge there has been a lack of information regarding to a direct comparison of single and two-phase AD of DCM in tropical ambient temperature. Therefore, the aim of this current study was to evaluate the process performance of single and two-phase biodigesters treating DCM and working in this specific area.…”
Section: Introductionmentioning
confidence: 99%
“…Energies 2021, 14, 5423 5 of 14 Composition analysis of the produced biogas and VFAs was carried out in a gas chromatograph (Agilent Technologies 7890A), as described in detail by previous studies [19,30].…”
Section: Analytical Determinationsmentioning
confidence: 99%
“…The average removal of COD was 98.5%, whereas the biogas production was higher than 10 times the reactor volume. Tsigkou et al [19] examined the one-and two-stage (CSTRs) system performance of the carbohydrate-rich substrates (fruits/vegetables mixture and disposable nappies hydrolysate) anaerobic co-digestion, concluding that the two-stage configuration resulted in a 18.4% higher yield in terms of energy production. Additionally, according to Sakarika et al [53], the end-of-life dairy products and agro-waste co-digestion resulted in a 30% higher energy efficiency in a two-stage system, compared to the one-stage digester.…”
Section: Cheese Whey Treatmentmentioning
confidence: 99%
See 1 more Smart Citation